Kontaminasi Bakteri pada Sediaan Campuran Intravena di Bangsal Perawatan Rumah Sakit - Shinta Sari Dewi; Fita Rahmawati; Sylvia Utami Utami Tunjung Pratiwi (Fakultas Farmasi Universitas Andalas, 2018)
Administration of intravenous admixtures with bacterial contamination during preparation and injection to the patient can cause nosocomial infection. The purpose of this study is to determine the frequency of bacterial contamination and the types of the bacteria which contaminate to the intravenous admixtures. The sampling was carried out in the treatment ward, Government Hospital in Yogyakarta. The bacterial contamination was determined by using sterility test with direct inoculation method. A total of 60 intravenous admixtures were collected consisting of 43 intravenous admixtures were prepared by nurse in treatment ward and 17 intravenous admixtures were prepared by pharmacist in clean room. The frequency of bacterial contamination was identified in 1 of 43 (2.3%) prepared in treatment ward and none of the intravenous admixtures (0%) prepared in clean room. Enterobacter cloacae and Staphylococcus aureus were detected in one sample. Although sanitation and the training of aseptic technique can reduce the risk of bacterial contamination in treatment ward, but by using clean room to prepare intravenous admixtures can be the best strategy